A study on the relationship between correlation coefficient and inverse regression / Ng Set Foong and Teoh Sian Hoon - Ng, Set Foong; Teoh, Sian Hoon (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
This paper focuses on the use of an inverse regression model. The discussion provides an idea on how correlation coefficient, r, in a regression analysis plays an important role in estimation of the value of independent variable X based on the known value of Y. The construction of an inverse regression mode is further illustrated. This issue is discussed in detail with analysis using SPSS software.